Gim Berbasis Open Source Software sebagai Media Pembelajaran Guru PAUD - Bayu Indra Pratama; Rachmat Kriyantono; Dessanti Putri Sekti Ari (Jurnal Pengabdian Masyarakat (abdira), 2022)
Early childhood education teachers need to develop varied learning methods. Diverse learning methods can encourage students' interest in learning. The use of information technology is one of the methods and learning media that can be used. Teachers must be smart in choosing to use applications, so there needs to be the development of learning methods for early childhood teachers with open source licensed games. The use of open source applications can prevent teachers from abusing copyright. Based on the analysis of the existing problems, the team is of the view that it is necessary to socialize the use of games as a learning medium for PAUD teachers at Insan Permata Kindergarten, Malang City. This form of socialization is packaged in the form of an application use workshop that allows participants to learn directly. The form of the workshop is carried out using a ToT (Traning of Trainer) scheme. The findings of this workshop show that legality and cost aspects are actually a problem in the application of game applications. The price of educational computer games tends to be expensive. The use of computer games with open source licenses provides opportunities for variations in the applications used.